THE ROLE OF SERVICE QUALITY ON LOYALTY AMONG LOW COST CARRIER CONSUMER - Dion Nardo Julius; Devi Jatmika (Psibernetika, 2019)
ABSTRACT. As one of the peoples choice for traveling, "X" airline company is one of low cost carrier in Indonesia is considered to have poor service quality despite controlling nearly 60% of domestic market share. The purpose of this study was to determine whether there is influence of service quality on customer loyalty among "X" airline company. The method used is causal comparative quantitative research. Data were collected through a questionnaire with a sample size of 250 people aboard with "X" airline company. Purposive sampling technique was used in this research. The results of this study indicate that there is a positive influence between service quality on customer loyalty with regression value of 0.802 (p = 0.000). Reliability, assurance and empathy dimensions are the three dimension that have the most impact on customer loyalty (p<0.05). Based on the results, it is recommended that the "X" airline company continue to strive to improve the quality of services, especially in terms of safety and comfort to create a customer loyalty.Keywords: service quality, customer loyalty, low cost carrier, passengers ABSTRAK. Sebagai salah satu pilihan masyarakat untuk berpergian, perusahaan penerbangan “X” adalah salah satu maskapai berbiaya rendah di  Indonesia yang dianggap memiliki kualitas layanan yang buruk meskipun menguasai hampir 60%  pangsa pasar domestik. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh kualitas layanan terhadap loyalitas konsumen perusahaan penerbangan “X”. Metode yang digunakan adalah penelitian kuantitatif kausal komparatif. Data dikumpulkan melalui kuesioner kepada sampel berjumlah 250 orang yang pernah menggunakan penerbangan maskapai penerbangan “X”. Teknik sampling purposive sampling digunakan dalam penelitian ii. Hasil penelitian menunjukkan bahwa ada pengaruh positif antara kualitas layanan terhadap loyalitas pelanggan dengan nilai regresi 0.802 (p=0.000). Dimensi reliabilitas, jaminan, dan empati adalah tiga dimensi yang paling berdampak terhadap loyalitas konsumen (p< 0.05).  Berdasarkan hasil, direkomendasikan agar perusahaan penerbangan “X” terus berusaha untuk meningkatkan kualitas layanan, terutama dalam hal keselamatan dan untuk menciptakan loyalitas konsumen.Kata kunci: kualitas layanan, loyalitas konsumen, low cost carrier, penumpang